TGFβ suppresses CD8+ T cell expression of CXCR3 and tumor trafficking - Andrew J. Gunderson; Tomoko Yamazaki; Kayla McCarty; Nathaniel Fox; Michaela Phillips; Alejandro Alice; Tiffany Blair; Mark Whiteford; David O’Brien; Rehan Ahmad; Maria X. Kiely; Amanda Hayman; et al. (Nature Communications, 2020)
TGFβ has a role in cancer immunosuppression but the exact mechanisms haven’t been fully elucidated. Here, using mouse models deficient in TGFβ-signaling, the authors show that loss of ALK5 in CD8 + T cells enhances their tumour trafficking and cytotoxicity suggesting that ALK5 inhibitors may have clinical utility.